2014
DOI: 10.1111/jwas.12151
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Plant Ethanolic Extracts against Fish Pathogens

Abstract: Fifteen commercial ethanolic extracts from medicinal plants were in vitro screened for antibacterial activity against Listonella anguillarum (serotypes O1 and O2), Yersinia ruckeri, Photobacterium damselae subsp. piscicida, and Lactococcus garvieae. Their antimicrobial potential was assessed by the disc diffusion assay, then minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were established by the broth microdilution method. The extracts of lavender, Lavandula officinalis; lem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 18 publications
2
20
0
1
Order By: Relevance
“…piscicida, Yersinia ruckeri, Lactococcus garvieae), and Rosmarinus officinalis indicated weak antimicrobial activity with inhibition zones 0.3 and 4.3 mm against Y. ruckeri and L. garvieae, respectively. But, Thymus vulgaris showed no inhibitory activity against L. garvieae, and demonstrated inhibition zone with 0.5 mm on growth of Y. ruckeri (Bulfon et al, 2014). In the study used the disk diffusion method, Starliper et al (2015) reported that the diameters of inhibition zone of 20% emulsions of TEO and REO against Aeromonas salmonicida subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…piscicida, Yersinia ruckeri, Lactococcus garvieae), and Rosmarinus officinalis indicated weak antimicrobial activity with inhibition zones 0.3 and 4.3 mm against Y. ruckeri and L. garvieae, respectively. But, Thymus vulgaris showed no inhibitory activity against L. garvieae, and demonstrated inhibition zone with 0.5 mm on growth of Y. ruckeri (Bulfon et al, 2014). In the study used the disk diffusion method, Starliper et al (2015) reported that the diameters of inhibition zone of 20% emulsions of TEO and REO against Aeromonas salmonicida subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, bacterial resistance against antibiotics increases over time and consequently decreases the effectiveness of antibiotics (Choudhury et al, 2005;Dubber and Harder, 2008;Stratev et al, 2018). There is, therefore, a growing interest in the identification of effective, new antibacterial agents that would serve as a new agent to use preventing bacterial diseases in aquaculture (Bansemir et al, 2004;Dubber and Harder, 2008;Bulfon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the in vitro assays indicated that P. ginseng extract exhibits antibacterial activity against Y. ruckeri and L. garvieae , with MIC values in agreement with our previously published data concerning the antibacterial properties of other ethanolic plant extracts (Bulfon et al . ). Such activity may be due to its content of saponins, tannins, flavonoids, alkaloids and polysaccharides (Cowan ; Tan & Vanitha ).…”
Section: Discussionmentioning
confidence: 97%
“…piscicida and Lactococcus garvieae (Bulfon et al, 2014). Tolmacheva et al (2014) applied aqueous and ethanolic extracts from Vaccinium vitis idaea in a radial growth inhibition assay against wild-type Chromobacterium violaceum ATCC 31532 and reporter Chromobacterium violaceum NCTC 13274 strains observed a prominent growth-inhibition activity.…”
Section: Discussionmentioning
confidence: 99%